2008
DOI: 10.1210/jc.2007-1834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity on the Risk for Polycystic Ovary Syndrome

Abstract: Our results suggest that the risk of PCOS is only minimally increased with obesity, although the degree of obesity of PCOS patients has increased, similar to that observed in the general population. These data indicate that obesity in PCOS reflects environmental factors to a great extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
191
5
22

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(226 citation statements)
references
References 33 publications
8
191
5
22
Order By: Relevance
“…This state corrects on its own after few years resulting into regular ovulatory cycles as the H-P-O axis matures. 1,2 In some young girls however anovulation persists and continues as chronic anovulation. The resulting hyperestrogenism, leads to hyperandrogenism, manifesting clinically as irregular menses, amenorrhea, menorrhagia, hirsutism, acne, oily skin, alopecia, obesity or a propensity for weight gain and multiple unruptured follicles in ovaries, collectively known as polycystic ovarian syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This state corrects on its own after few years resulting into regular ovulatory cycles as the H-P-O axis matures. 1,2 In some young girls however anovulation persists and continues as chronic anovulation. The resulting hyperestrogenism, leads to hyperandrogenism, manifesting clinically as irregular menses, amenorrhea, menorrhagia, hirsutism, acne, oily skin, alopecia, obesity or a propensity for weight gain and multiple unruptured follicles in ovaries, collectively known as polycystic ovarian syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperandrogenemia is a risk factor for MBS independent of obesity and insulin resistance, (IR), glucose intolerance, dyslipidemia, hypertension and central obesity. 1,2 Many ways of diagnosing PCOS have been described using various criteria. The NIH criteria defines PCOS as unexplained hyper androgenic anovulation, oligomenorrhea and hyperandrogenism ,either clinical or biochemical after excluding other causes of anovulation like hypothyroidism and hyperprolactinamia.…”
mentioning
confidence: 99%
“…(5,6). The different prevalence of obesity in the clinical series of women with PCOS almost certainly reflects the overall rates of obesity (30-70%) in different populations (24,25,26). Interestingly, it has been shown that obesity may also cluster in PCOS families (27).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…diagnosis, the prevalence of overweight and obesity in the PCOS population is above 50% in the United States [109] and between 30% and 50% in Europe [110]. Obesity by itself is associated with insulin resistance and compensatory hyperinsulinemia, which is worst following intra-abdominal accumulation of fat.…”
Section: Obesity and Pcos-atmentioning
confidence: 99%